Stato e Rivoluzione Big_Data - Amodio, Paolo (S&F_scienzaefilosofia.it, 2018)
STATE AND BIG_DATA REVOLUTION Our time is characterized by the deep transformation of the digital turn, where the new technologies of information, the so-called ICT, have introduced within the private and public space, some definitive changes. We are experiencing a real cultural revolution. What Luciano Floridi names as the fourth revolution, is the era in which the Data and their extraction, elaboration and management become the highest value. The generated Data follow an exponential flow: over the last year, according to some specialists, they have become bigger than the order of Zettabyte (1021 byte), a real record in the globalized Western world. The new frontier of Big Data, entities hard to define, shape complex system of data generated by instruments, sensors, Internet transactions, emails, videos, clicks and web interactions. This process demands new challenges for our interrogations and new theoretical needs in order to reconcile the technological complexity and our limited understanding.